A bidirectional high-frequency link inverter using center-tapped transformer - Ramli, Mohd zulkifli (2004)
In this paper, a bidirectional high-frequency link inverter is proposed. The main feature of the inverter is that the electrical isolation is provided by a high-frequency center-tapped transformer. Furthermore, the sinusoidal pulse width modulation method is modified so that the transformer can be utilized near to its full potential. As a result, the power switches count is reduced, and the efficiency increased. A 1 kW prototype inverter is built and typical results are presented